Measuring tourists’ satisfaction with multiple mosque destination attributes - Mohammad Roffe, Nor Afira Yasmin; Md Sawari, Siti Salwa (2019)
The developing of the mosque in Malaysia represent the socio-cultural of Muslim people. Besides being developed as a place for religious activities, the mosque also has other roles to function such as in Malaysia, the mosque was utilized space for learning activities as well as an education center. Mosque tourism can be tourist experience of travel that retreats from the hectic life with expectation and satisfaction. The aim of this paper is to investigate the significant relationship between destination attributes and tourist satisfaction in mosques destination. This study is a quantitative in nature, whereby researcher used questionnaire to assess the tourist satisfaction and mosque destination attributes. Non- probability sampling was used in this study. This method is a convenient sampling method process which is used to select the sample. The sample size for this study was 200 respondents. Pearson Correlation was employed to identify the relationship among the variables. From the analysis it was found that destination attributes have a positive relationship with tourist satisfaction on mosque destination in Malaysia. This research is necessary to provide a better understanding of the mosque destination attributes in Malaysia focused on tourists’ satisfaction in Islamic tourist destination